2006
DOI: 10.1113/jphysiol.2006.112706
|View full text |Cite
|
Sign up to set email alerts
|

Prior heavy exercise elevates pyruvate dehydrogenase activity and speeds O2 uptake kinetics during subsequent moderate‐intensity exercise in healthy young adults

Abstract: The adaptation of pulmonary oxygen uptake (V O 2 ) during the transition to moderate-intensity exercise (Mod) is faster following a prior bout of heavy-intensity exercise. In the present study we examined the activation of pyruvate dehydrogenase (PDHa) during Mod both with and without prior heavy-intensity exercise. Subjects (n = 9) performed a Mod 1 -heavyintensity-Mod 2 exercise protocol preceded by 20 W baseline. Breath-by-breathV O 2 kinetics and near-infrared spectroscopy-derived muscle oxygenation were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 61 publications
(101 reference statements)
3
57
1
Order By: Relevance
“…A number of studies have measured τVO 2p values in young untrained men (Berger et al, 2006b;Gurd et al, 2006Gurd et al, , 2008Koppo et al, 2004;McKay et al, 2009;Murias et al, 2010; our group mean τVO 2p values in young (26 s) are in agreement with these studies which reported a range between 21 and 34 s. Additionally, a number of studies have examined τVO 2p values in older untrained men (Berger et al, 2006a;Chilibeck et al, 1996;Gurd et al, 2008;Murias et al, 2010); our group mean τVO 2p values in the old untrained (42 s)…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A number of studies have measured τVO 2p values in young untrained men (Berger et al, 2006b;Gurd et al, 2006Gurd et al, , 2008Koppo et al, 2004;McKay et al, 2009;Murias et al, 2010; our group mean τVO 2p values in young (26 s) are in agreement with these studies which reported a range between 21 and 34 s. Additionally, a number of studies have examined τVO 2p values in older untrained men (Berger et al, 2006a;Chilibeck et al, 1996;Gurd et al, 2008;Murias et al, 2010); our group mean τVO 2p values in the old untrained (42 s)…”
Section: Discussionsupporting
confidence: 80%
“…Conflicting evidence exists in the literature in both human and canine models. By increasing the activation of PDH via a pharmacological intervention (dichloroacetate: DCA) or heavy-priming exercise there was a significant decrease of the contribution of substrate-level phosphorylation during MOD (Gurd et al, 2006;Howlett et al, 1999). These findings would suggest that the reduction of substrate-level phosphorylation would stem from a more rapid activation of both oxidative phosphorylation and muscle O 2 utilization.…”
Section: Near-infared Spectroscopymentioning
confidence: 77%
“…However, the effects of prior exercise on PCr breakdown appear to be less consistent in the literature. Studies have demonstrated that [PCr] is higher (Campbell-O'Sullivan et al 2002;Rossiter et al 2001), lower (Sahlin et al 2005), or unchanged (Gurd et al 2006) during the early stages of a subsequent bout of exercise compared to corresponding times during the initial bout of exercise. These apparent contradictions in the literature may be related to the method of measurement (Phosphorus-31 magnetic resonance spectroscopy, 31 P-MRS vs. muscle biopsy), intensity of prior exercise, recovery time between exercise bouts, and the intracellular hydrogen ion concentration ([H + ] i ) at the onset of the subsequent exercise.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have shown that prior heavy-intensity exercise either accelerates (e.g., Fukuba et al 2004;Gurd et al 2006;Paterson et al 2005;Rossiter et al 2001) or increases the amplitude (e.g., Burnley et al 2002Burnley et al , 2006 of the fundamental, phase II VO 2 kinetic response, reflecting muscle O 2 consumption (Grassi et al 1996). Furthermore, during heavy-intensity exercise performed in a supine or prone position, where muscle perfusion pressure is reduced, studies have consistently suggested that O 2 availability is a limiting factor of muscle O 2 consumption at the onset of exercise (Endo et al 2005;Fukuba et al 2004;Hughson et al 1993;Jones et al 2006;Perrey et al 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Among these, increased muscle oxygen delivery may play a crucial role for its potentially direct effect (DeLorey et al 2007;Endo et al 2005;Faisal et al 2009), although enhanced activity of muscle oxidative enzymes and alterations of motor unit recruitment patterns have also been considered (for a review of these alternative hypotheses, see Poole and Jones 2012). According to Faisal et al (2009), greater oxygen delivery with increased leg blood flow after prior heavy exercise (Fukuba et al 2007), or an elevation in pyruvate dehydrogenase and intracellular lactate and acetyl CoA concentrations (Gurd et al 2006), may generate an increase in PO 2 following elevated oxygen delivery.…”
Section: The Effect Of Priming Exercisementioning
confidence: 97%